Preparation method of hydrogenation catalyst

By simplifying the process steps, reacting molybdenum-nickel waste catalyst with chlorine and sonication, combined with impregnation technology of pseudo-thin aluminite and boron sources, the activity and life of the hydrogenation catalyst were successfully improved, and the problems of low recycling rate and short catalyst activity in the prior art were solved.

CN119819378APending Publication Date: 2025-04-15CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202311317028.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-12
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The existing hydrogenation catalyst recovery and reuse methods have problems such as complex process steps, low recycling rate of active metals and/or support, and low activity and short life of the prepared catalyst.

Method used

The molybdenum-nickel-based waste catalyst is extracted and removed, crushed, reacted with chlorine, sonicated, and then kneaded with pseudo-thin alumina, dried and calcined to form a catalyst support. Then, the solution of the boron source and polyol is first impregnated with the support, and then impregnated with a second impregnation solution of Group VIII metal and organic acid to obtain a high activity and long-lived hydrogenation catalyst.

Benefits of technology

The efficient recycling and utilization of metal components and alumina support in nickel-molybdenum waste catalysts is achieved. The new catalyst obtained has high activity and long life, and is suitable for the recycling and reuse of nickel-molybdenum catalysts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004489663220000081
    Figure BDA0004489663220000081
  • Figure BDA0004489663220000082
    Figure BDA0004489663220000082
  • Figure BDA0004489663220000083
    Figure BDA0004489663220000083
Patent Text Reader

Abstract

The invention discloses a preparation method of a hydrogenation catalyst. The method comprises the following steps: (1) crushing a solid obtained after extraction and oil removal of the molybdenum-nickel waste catalyst; (2) reacting the catalyst powder with chlorine, cooling, transferring into an anhydrous organic solvent for ultrasonic treatment, and separating to obtain a solvent I and a material II; (3) mixing, kneading and molding the material II and pseudo-boehmite, drying and roasting to obtain a catalyst carrier; (4) dropwise adding a solvent I into a solution containing a boron source and polyol to obtain a first impregnation liquid, impregnating the first impregnation liquid onto the carrier in the step (3), and drying and roasting to obtain a catalyst intermediate; and (5) impregnating the catalyst intermediate in a second impregnation liquid containing a group VIII metal and an organic acid, and drying to obtain the hydrogenation catalyst. According to the method, the metal components and the alumina carrier of the nickel-molybdenum waste catalyst can be efficiently utilized, and the obtained new catalyst is high in activity and long in service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of hydrogenation catalysts, and specifically relates to a method for preparing a hydrogenation catalyst. Background Art

[0002] At present, hydroprocessing catalysts mainly use molybdenum and nickel as active components and alumina as carrier, and are widely used in petroleum refining and chemical industries. However, after a certain period of use, the catalyst will gradually lose its activity due to carbon deposition and metal deposition, resulting in a large amount of waste catalyst. Since waste hydrogenation catalysts are rich in valuable metal elements, they have high economic value. Therefore, it is very necessary to recycle and reuse the active metals and alumina carriers in waste hydrogenation catalysts to realize the resource utilization of waste hydrogenation catalysts, solve their pollution problems to the environment, and achieve good social and ecological benefits.

[0003] CN108067272A discloses a method for preparing a hydrogenation catalyst. The method comprises: (1) extracting, microwave treating and crushing molybdenum-nickel waste hydrogenation catalyst; (2) uniformly mixing the catalyst powder crushed in step (1) with alkali and calcining at high temperature; (3) soaking the waste catalyst after calcination in step (2) in hot water; (4) reacting the filtrate in step (3) with an acidic solution to prepare pseudo-boehmite, kneading, shaping and calcining the pseudo-boehmite to obtain a carrier; (5) adding Na to the solution filtered in step (4); 2 S solution to obtain MoO 3 ; (6) adding acid to the solid after filtration in step (3), then using alkaline solution to remove Fe and Al in the solution, and finally preparing basic nickel carbonate; (7) preparing molybdenum-nickel-phosphorus solution with molybdenum oxide in step (5) and basic nickel carbonate in step (6), impregnating the carrier in step (4), and preparing hydrogenation catalyst after drying and roasting. This method is suitable for recycling waste molybdenum-nickel catalyst to prepare new catalyst, but the process of this method is too complicated, and there is a problem of low recovery rate of carrier and metal.

[0004] In summary, the existing methods for recycling and reusing hydrogenation catalysts have problems to varying degrees, such as complicated process steps, low recycling rate of active metals and / or carriers, and low activity and short life of the prepared catalysts. Therefore, further in-depth research on the recycling and utilization of spent hydrogenation catalysts is of great significance. Summary of the invention

[0005] In view of the deficiencies of the prior art, the present invention provides a method for preparing a hydrogenation catalyst. The method of the present invention can efficiently utilize the metal components and alumina carrier of the nickel-molybdenum series waste catalyst. The method of the present invention has simple recovery steps, can efficiently utilize the metal components and alumina carrier of the nickel-molybdenum series waste catalyst, and the obtained new catalyst has high activity and long service life, and is particularly suitable for the recovery and reuse of nickel-molybdenum series catalysts.

[0006] The present invention provides a method for preparing a hydrogenation catalyst, the method comprising the following steps:

[0007] (1) crushing the solid after extracting and removing oil from the molybdenum-nickel waste catalyst;

[0008] (2) After the catalyst powder reacts with chlorine, it is cooled and transferred to an anhydrous organic solvent for ultrasonic treatment to separate solvent I and material II;

[0009] (3) kneading material II and pseudo-boehmite into a mixture, drying, and calcining to obtain a catalyst carrier;

[0010] (4) adding solvent I dropwise to a solution containing a boron source and a polyol to obtain a first impregnation solution, impregnating the first impregnation solution onto the support of step (3), and drying and calcining to obtain a catalyst intermediate;

[0011] (5) The catalyst intermediate is impregnated with a second impregnation solution containing a Group VIII metal and an organic acid, and then dried to obtain a hydrogenation catalyst.

[0012] According to the present invention, the waste hydrogenation catalyst in step (1) is a nickel-molybdenum waste catalyst, that is, a molybdenum-nickel catalyst deactivated after residual oil hydrogenation treatment. The waste hydrogenation catalyst includes 70% to 90% of catalyst solids and 10% to 30% of petroleum fractions by weight. Further, the waste hydrogenation catalyst after extraction and deoiling, based on the catalyst mass and in terms of mass fraction, includes:

[0013] 10% to 25% molybdenum calculated as molybdenum trioxide;

[0014] 3% to 10% nickel, calculated as nickel oxide;

[0015] 3% to 10% vanadium, calculated as vanadium pentoxide;

[0016] 6% to 14% carbon;

[0017] 41% to 77% carrier alumina.

[0018] According to the present invention, the organic solvent used for extraction in step (1) includes one or more of toluene, petroleum ether, and ethanol; the extraction temperature is 80-110° C., and the extraction time is 60-90 hours. The mass ratio of organic solvent to catalyst is 25-50:1. The extraction is used to remove the petroleum fraction in the nickel-molybdenum waste catalyst.

[0019] According to the present invention, in step (1), the waste hydrogenation catalyst is extracted and then dried and crushed. The drying temperature is 120-200° C. and the drying time is 3-8 hours. The crushing is to crush the waste hydrogenation catalyst to a particle size of 200-500 mesh, preferably 300-400 mesh.

[0020] According to the present invention, the purity of the chlorine gas in step (2) is 96% or more by volume. The flow rate of the chlorine gas in step (2) is 2.7 to 6.8 mL / (min·g catalyst); the reaction conditions are as follows: the reaction temperature is 300 to 400° C., and the reaction time is 40 to 90 min.

[0021] According to the present invention, in step (2), the mixture is cooled to a temperature required for ultrasonic treatment. The anhydrous organic solvent is one or more selected from acetone, tetrahydrofuran, and acetic acid. The mass ratio of the anhydrous organic solvent to the catalyst powder is 3 to 5:1.

[0022] According to the present invention, the ultrasonic frequency in step (2) is 10KHz to 150KHz, the ultrasonic treatment temperature is 20°C to 70°C, and the treatment time is 0.5 to 2h.

[0023] According to the present invention, the mass ratio of the pseudo-boehmite in step (3) to material II is 7 to 13:15 to 30 in terms of alumina. The kneading molding described in step (3) is carried out by conventional methods in the art. During the molding process, adhesives, extrusion aids and water can be added as needed. The adhesive can be at least one of nitric acid, acetic acid, and citric acid, and the extrusion aid can be sesbania powder. The amount of the adhesive and extrusion aid added is added according to the actual molding needs, and the present invention has no special requirements. For example, the amount of the adhesive added is 0.5wt% to 4.0wt% of the raw material mass. The amount of the extrusion aid added is 0.5wt% to 5.0wt% of the raw material mass. The amount of water added is 85wt% to 100wt% of the raw material mass.

[0024] According to the present invention, in step (3), the drying temperature is 120-160° C., the drying time is 2-6 hours, the roasting temperature is 550-750° C., and the roasting time is 2-6 hours.

[0025] According to the present invention, in step (4), the boron source is boric acid, the polyol is one or more of 1,4-butanediol, 1,3-propylene glycol, tetramethylene glycol, glycerol, polyethylene glycol (molecular weight is less than 2000) and diethylene glycol. The mass ratio of the boric acid to the polyol is 2:1 to 4:1.

[0026] According to the present invention, in step (4), the time for adding solvent I dropwise to the solution containing the boron source and the polyol is 30 to 180 minutes, preferably 60 to 120 minutes. After the dropwise addition, stirring is continued for 20 to 60 minutes.

[0027] According to the present invention, the impregnation in step (4) can be carried out by spray impregnation, and the impregnation can be carried out by equal volume impregnation or supersaturated impregnation, preferably equal volume impregnation. The drying conditions are as follows: the drying temperature is 100-160°C, and the drying time is 1-8h; the roasting conditions are as follows: the roasting temperature is 450-650°C, and the roasting time is 2-7h.

[0028] According to the present invention, in step (5), the Group VIII metal is nickel, and the concentration of the nickel source in the second impregnation solution is 40 to 120 g / L in terms of nickel oxide. The nickel source is from soluble salts, such as at least one of nitrates, monohydrogen phosphates, and dihydrogen phosphates; the organic acid is at least one of citric acid, malic acid, acetic acid, formic acid, malonic acid, and succinic acid. The molar ratio of the organic acid to the Group VIII element is 0.5:1 to 2:1, preferably 0.8:1 to 1.5:1.

[0029] According to the present invention, the impregnation in step (5) can be carried out by a spraying method, and the impregnation can be carried out by an equal volume impregnation method or a supersaturated impregnation method, preferably an equal volume impregnation method; the drying condition is drying at 100 to 160° C. for 1 to 8 hours. Further, curing can be carried out before drying. The curing is to place the impregnated carrier in a closed container at 10 to 30° C. for 6 to 12 hours. The curing pressure is not particularly limited and can be autogenous pressure.

[0030] According to the present invention, the composition of the hydrogenation catalyst in step (5), based on the mass of the catalyst and measured by mass fraction, includes:

[0031] Calculated as molybdenum trioxide, the content of Mo in terms of oxide is 5.0% to 22.0%.

[0032] Calculated as nickel oxide, the content of Ni is 3% to 9%.

[0033] Calculated as vanadium pentoxide, the vanadium content is 0.2% to 3.0%.

[0034] Calculated as phosphorus pentoxide, the phosphorus content is 0.5% to 4.0%.

[0035] Calculated as boron trioxide, the boron content is 0.1% to 0.5%.

[0036] The content of organic acid is 0.5% to 2.5%,

[0037] The content of aluminum oxide is 59.0% to 90.0%.

[0038] According to the present invention, the properties of the catalyst in step (5) are as follows: the specific surface area is 170 to 280 m 2 / g, the pore volume is 0.6~1.3mL / g, the average pore diameter is 9~15nm, and the mechanical strength is 150~200N / cm.

[0039] Another aspect of the present invention provides a hydrogenation catalyst prepared by the above method. Preferably, the hydrogenation catalyst is a residue oil hydrodemetallization catalyst or a residue oil hydrodesulfurization catalyst.

[0040] Compared with the prior art, the present invention has the following advantages:

[0041] In the method of the present invention, by controlling the reaction conditions, the catalyst powder can react with chlorine, and molybdenum can be simply and highly selectively extracted from the catalyst and transferred to the solvent phase. The solvent phase is then added dropwise to a solution containing a boron source and a polyol to obtain a first impregnation solution. While effectively extracting molybdenum, the carbon deposits in the waste catalyst can be effectively retained in the carrier component. The carrier component is mixed with pseudo-boehmite and calcined to obtain a carrier and the carbon deposits are removed at the same time. Finally, the first impregnation solution is loaded on the carrier and calcined, and then impregnated with a second impregnation solution of a Group VIII metal and an organic acid to obtain a catalyst, which is beneficial to adjusting the pore structure of the catalyst and increasing the surface area of ​​the carrier. The number of acid sites can produce more coordinated unsaturated sites. On the other hand, the loading of active components can be adjusted, especially reducing the amount of molybdenum entering the small pores, and loading it more evenly on the carrier surface in the form of +5-valent molybdenum, which is easier to be sulfurized to +4-valent MoS 2 , which accelerates the formation of MoS 2 The rate of the complexing agent is reduced, and the addition of the complexing agent delays the sulfidation of Ni, making it easier to form MoS in the catalyst. 2 The skeleton and the efficient hydrogenation active phase structure of metallic nickel on the outer surface are beneficial to improving the activity and stability of the catalyst. DETAILED DESCRIPTION

[0042] The effects and effects of the present invention are further illustrated below by way of examples, but the following examples do not constitute a limitation of the method of the present invention.

[0043] In the present invention, % refers to mass fraction unless otherwise specified.

[0044] In the present invention, the specific surface area, pore volume and pore distribution are measured by using an ASAP2420 fully automatic physical adsorption instrument from Micromeritics Instruments, Inc., USA. The measurement method is as follows: After the sample is treated at 300°C and 0.1 MPa for 4 h, the liquid N 2As adsorbent, the adsorption temperature is -196℃, and the analysis test is carried out after accurate weighing. The specific surface area is calculated according to the BET method, and the pore volume and pore distribution are calculated according to the BJH method.

[0045] In the present invention, the catalyst composition is tested by spectrophotometry, and the testing instrument is a Lambda 365 ultraviolet spectrophotometer.

[0046] In the present invention, the composition and properties of the catalyst prepared in each example are shown in Table 1.

[0047] In the present invention, the composition of the spent hydrogenation catalyst used in each example is calculated by mass fraction as follows: 85% of catalyst solids and 15% of petroleum fractions.

[0048] In the present invention, the extraction and deoiling conditions of each example are: the organic solvent is toluene, the extraction temperature is 100°C, the extraction time is 72h, and the mass ratio of the organic solvent to the catalyst is 30:1. The composition of the waste hydrogenation catalyst after extraction and deoiling is calculated by mass fraction:

[0049] 19.2% molybdenum as molybdenum trioxide;

[0050] 8.6% nickel, calculated as nickel oxide;

[0051] 4.2% vanadium as vanadium pentoxide;

[0052] 9.1% Carbon,

[0053] The balance is carrier alumina.

[0054] Example 1

[0055] (1) Take the spent hydrogenation catalyst after industrial operation, extract and remove oil, dry it at 120℃ for 6h, and then crush it into 300 mesh.

[0056] (2) 334 g of catalyst powder was placed in a container, and 3.9 mL / (min·g catalyst) of 98% purity chlorine gas was introduced for reaction at a temperature of 350° C. and a reaction time of 80 min. The reacted catalyst was cooled to 30° C., then transferred to 1169 g of acetone and mixed evenly, and then placed in an ultrasonic generator, with acetone as the medium, and treated at 30° C. and an ultrasonic frequency of 50 KHz for 1 hour, and separated to obtain solvent I and material II, respectively. Material II was 269 g.

[0057] (3) Take 179 g of pseudo-boehmite (with an aluminum oxide mass content of 69.1%), material II (269 g) obtained in step (2), 9 g of sesbania powder, 4.5 g of nitric acid, and 428 g of water, mix and knead them into shape, dry them at 120°C for 3 hours, and calcine them at 700°C for 4 hours to obtain catalyst carrier A-0.

[0058] (4) Add solvent I dropwise to a solution containing 5.6 g of boric acid and 2.5 g of 1,4-butanediol for 90 min. Stir for 30 min to obtain impregnation solution L-0. Spray the impregnation solution L-0 onto carrier A-0, dry at 130°C for 4 hours, and calcine at 500°C for 3 hours to obtain A-1.

[0059] (5) Weigh 21 g of nickel nitrate hexahydrate and 6.3 g of acetic acid, dissolve in 100.0 mL of water, and record the resulting solution as L-1. Use a spraying method to impregnate the above impregnation solution L-1 on the carrier A-1 to obtain DA-1. After DA-1 is placed in a closed container at room temperature 20°C for 6 hours, it is dried at 120°C for 4 hours to obtain CA-1. The composition of catalyst CA-1 is shown in Table 1.

[0060] Example 2

[0061] (1) Take the spent hydrogenation catalyst after industrial operation, extract and remove oil, dry it at 140°C for 4 hours, and then crush it into 500 mesh.

[0062] (2) 298 g of catalyst powder was placed in a container, and 6.3 mL / (min·g catalyst) of 99% by volume chlorine gas was introduced for reaction at a reaction temperature of 350° C. and a reaction time of 50 min. The catalyst after the reaction was cooled to 30° C., then transferred to 1192 g of tetrahydrofuran, mixed evenly, and placed in an ultrasonic generator, using tetrahydrofuran as a medium, and treated at 50° C. and an ultrasonic frequency of 100 KHz for 2 hours, and separated to obtain solvent I and material II, respectively. Material II was 240 g.

[0063] (3) Take 184 g of pseudo-boehmite (with an aluminum oxide mass content of 69.1%), material II (240 g) obtained in step (2), 6 g of sesbania powder, 7.2 g of nitric acid, and 408 g of water, mix and knead into shape, dry at 120°C for 4 hours, and calcine at 750°C for 3 hours to obtain catalyst carrier B-0.

[0064] (4) Solvent I was added dropwise to a solution containing 4.5 g of boric acid and 2.0 g of 1,4-butanediol for 60 min. The solution was stirred for 30 min to obtain impregnation solution L-0. The impregnation solution L-0 was impregnated on carrier B-0 by spraying, dried at 120° C. for 4 hours, and calcined at 480° C. for 3 hours to obtain B-1.

[0065] (5) Weigh 20 g of nickel nitrate hexahydrate and 4.2 g of acetic acid, dissolve in 100.0 mL of water, and record the resulting solution as L-1. Use a spraying method to impregnate the above impregnation solution L-1 on the carrier B-2 to obtain DB-2. After DB-2 is placed in a closed container at room temperature 20°C for 6 hours, it is dried at 120°C for 4 hours to obtain CB-2. The composition of catalyst CB-2 is shown in Table 1.

[0066] Example 3

[0067] (1) Take the spent hydrogenation catalyst after industrial operation, extract and remove oil, dry it at 120℃ for 6h, and then crush it into 300 mesh.

[0068] (2) 334 g of catalyst powder was placed in a container, and 3.9 mL / (min·g catalyst) of 98% by volume chlorine gas was introduced for reaction at a reaction temperature of 400° C. and a reaction time of 80 min. The catalyst after the reaction was cooled to 30° C., then transferred to 1336 g of acetic acid, mixed evenly, and placed in an ultrasonic generator, with acetic acid as the medium, and treated at 30° C. and an ultrasonic frequency of 120 KHz for 1 hour, and separated to obtain solvent I and material II, respectively. Material II was 269 g.

[0069] (3) Take 179 g of pseudo-boehmite (with an aluminum oxide mass content of 69.1%), material II (269 g) obtained in step (2), 9 g of sesbania powder, 4.5 g of nitric acid, and 428 g of water, mix and knead into shape, dry at 130° C. for 3 hours, and calcine at 730° C. for 4 hours to obtain catalyst carrier C-0.

[0070] (4) Solvent I was added dropwise to a solution containing 6 g of boric acid and 1.5 g of 1,3-propylene glycol for 120 min. The solution was stirred for 30 min to obtain impregnation solution L-0, which was impregnated onto carrier C-0 by spraying, dried at 130° C. for 4 hours, and calcined at 480° C. for 3 hours to obtain C-1.

[0071] (5) Weigh 10.3 g of nickel nitrate hexahydrate and 2.9 g of acetic acid, dissolve in 60.0 mL of water, and record the resulting solution as L-1. Use a spraying method to impregnate the above impregnation solution L-1 on the carrier C-1 to obtain DC-1. After DC-1 is placed in a closed container at room temperature 20°C for 6 hours, it is dried at 120°C for 4 hours to obtain CC-1. The composition of catalyst CC-1 is shown in Table 1.

[0072] Example 4

[0073] (1) Take the spent hydrogenation catalyst after industrial operation, extract and remove oil, dry it at 120℃ for 6h, and then crush it into 300 mesh.

[0074] (2) 400 g of catalyst powder was placed in a container, and 5.3 mL / (min·g catalyst) of 98% purity chlorine gas was introduced for reaction at a reaction temperature of 300° C. and a reaction time of 60 min. The catalyst after the reaction was cooled to 30° C., then transferred to 1760 g of acetone and mixed evenly, and then placed in an ultrasonic generator, with acetone as the medium, and treated at 30° C. and an ultrasonic frequency of 50 KHz for 1 hour, and separated to obtain solvent I and material II, respectively. Material II was 323 g.

[0075] (3) Take 184 g of pseudo-boehmite (with an aluminum oxide mass content of 69.1%), material II (323 g) obtained in step (2), 9 g of sesbania powder, 4.5 g of nitric acid, and 450 g of water, mix and knead them into shape, dry them at 120° C. for 3 hours, and calcine them at 700° C. for 4 hours to obtain catalyst carrier D-0.

[0076] (4) Add solvent I dropwise to a solution containing 4 g of boric acid and 2 g of propylene glycol for 90 min. Stir for 30 min to obtain impregnation liquid L-0, impregnate the carrier D-0 with the impregnation liquid L-0 by spraying, dry at 130° C. for 4 hours, and calcine at 485° C. for 3 hours to obtain D-1.

[0077] (5) Weigh 18 g of nickel nitrate hexahydrate and 4 g of acetic acid, dissolve in 100.0 mL of water, and record the resulting solution as L-1. Use a spraying method to impregnate the above impregnation solution L-1 on the carrier D-1 to obtain DD-1. After DD-1 is placed in a closed container at room temperature 20°C for 6 hours, it is dried at 120°C for 4 hours to obtain CD-1. The composition of catalyst CD-1 is shown in Table 1.

[0078] Comparative Example 1

[0079] Compared with Example 1, only the chlorine gas in step (2) is replaced by air. The other steps are the same as in Example 1.

[0080] A comparative hydrogenation catalyst DCA-1 was prepared.

[0081] Comparative Example 2

[0082] Compared with Example 1, the fresh catalyst before deactivation was used for comparison.

[0083] A comparative hydrogenation catalyst DCA-2 was prepared.

[0084] Comparative Example 3

[0085] Compared with Example 1, the difference is that in step (3), no pseudo-boehmite is added, but material II is directly mixed with an adhesive, an extrusion aid and water to form a kneaded shape.

[0086] A comparative hydrogenation catalyst DCA-3 was prepared.

[0087] Comparative Example 4

[0088] Compared with Example 1, the difference is that no organic acid is added during the preparation of the impregnation solution in step (5).

[0089] A comparative hydrogenation catalyst DCA-4 was prepared.

[0090] Comparative Example 5

[0091] Compared with Example 1, the difference is that in step (4), no boron source and polyol are added, and only solvent I is used as the first impregnation liquid to prepare a comparative hydrogenation catalyst DCA-5.

[0092] Comparative Example 6

[0093] Steps (1) to (3) of this example are the same as those of Example 1. Steps (4) and (5) in Example 1 are replaced by the following step A. Step A in this example is as follows: the impregnation liquid in this example is a mixture of the first impregnation liquid L-0 and the second impregnation liquid L-1 in Example 1. The catalyst carrier of step (3) is then impregnated with the above impregnation liquid, dried at 130°C for 4 hours, and calcined at 500°C for 3 hours to obtain the catalyst DCA-6.

[0094] Table 1 Composition of the catalyst obtained in each example

[0095]

[0096] Table 2 Properties of the catalysts obtained in each example

[0097]

[0098] Catalyst evaluation

[0099] The catalysts obtained in the examples and comparative examples were evaluated using the feedstock oils listed in Table 3. The reaction conditions are shown in Table 3, and the evaluation results are shown in Table 4.

[0100] Table 3 Raw oil properties and reaction conditions

[0101]

[0102]

[0103] Table 4 Evaluation results of catalysts of various examples

[0104] Removal rate Operation time, h Example 1 Example 2 Example 3 Example 4 HDM, % 200 98.1 98.3 98.5 98.3 HDM, % 2000 88.4 88.3 88.3 88.6 HDS, % 200 94.6 95.3 94.8 95.2 HDS, % 2000 83.6 83.5 84.4 83.5 HDN, % 200 84.7 81.4 82.6 83.5 HDN, % 2000 71.5 72.6 73.3 72.6

[0105] Table 3

[0106]

[0107] The above describes the specific implementation of the present invention in detail, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the various technical features being combined in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for preparing a hydrogenation catalyst, comprising the following steps: (1) crushing the solid after extracting and removing oil from the molybdenum-nickel waste catalyst; (2) After the catalyst powder reacts with chlorine, it is cooled and transferred to an anhydrous organic solvent for ultrasonic treatment to separate solvent I and material II; (3) kneading material II and pseudo-boehmite into a mixture, drying, and calcining to obtain a catalyst carrier; (4) adding solvent I dropwise to a solution containing a boron source and a polyol to obtain a first impregnation solution, impregnating the first impregnation solution onto the support of step (3), and drying and calcining to obtain a catalyst intermediate; (5) The catalyst intermediate is impregnated with a second impregnation solution containing a Group VIII metal and an organic acid, and then dried to obtain a hydrogenation catalyst.

2. The method according to claim 1, characterized in that: The spent hydrogenation catalyst after extraction and deoiling in step (1), based on the mass of the catalyst and calculated by mass fraction, comprises: 10% to 25% molybdenum calculated as molybdenum trioxide; 3% to 10% nickel, calculated as nickel oxide; 3% to 10% vanadium, calculated as vanadium pentoxide; 6% to 14% carbon; 41% to 77% carrier alumina.

3. The method according to claim 1, characterized in that: The purity of the chlorine gas in step (2) is greater than 96% by volume; And / or, the flow rate of chlorine gas in step (2) is 2.7 to 6.8 mL / (min·g catalyst).

4. The method according to claim 1, characterized in that: The reaction conditions in step (2) are as follows: the reaction temperature is 300-400° C., and the reaction time is 40-90 min.

5. The method according to claim 1, characterized in that: The ultrasonic frequency in step (2) is 10KHz to 150KHz; and / or the ultrasonic treatment temperature is 20°C to 70°C, and the treatment time is 0.5 to 2h.

6. The method according to claim 1, characterized in that: The mass ratio of the pseudo-boehmite in step (3) to material II is 7-13:15-30 in terms of alumina.

7. The method according to claim 1, characterized in that: The boron source in step (4) is boric acid; And / or, the polyol is one or more of 1,4-butanediol, 1,3-propylene glycol, tetramethylene glycol, glycerol, polyethylene glycol and diethylene glycol; And / or, the mass ratio of the boric acid to the polyol is 2:1 to 4:

1.

8. The method according to claim 1, characterized in that: In step (5), the Group VIII metal is nickel; and / or, in the second impregnation solution, the concentration of the nickel source is 40 to 120 g / L; And / or, the nickel source is from a soluble salt, such as at least one of nitrate, monohydrogen phosphate, and dihydrogen phosphate; and / or the organic acid is at least one of citric acid, malic acid, acetic acid, formic acid, malonic acid, and succinic acid; And / or, the molar ratio of the organic acid to the Group VIII element is 0.5:1 to 2:1, preferably 0.8:1 to 1.5:

1.

9. The method according to claim 1, characterized in that: The composition of the hydrogenation catalyst in step (5), based on the mass of the catalyst and measured by mass fraction, includes: Calculated as molybdenum trioxide, the content of Mo in terms of oxide is 5.0% to 22.0%. Calculated as nickel oxide, the content of Ni is 3% to 9%. Calculated as vanadium pentoxide, the vanadium content is 0.2% to 3.0%. Calculated as phosphorus pentoxide, the phosphorus content is 0.5% to 4.0%. Calculated as boron trioxide, the boron content is 0.1% to 0.5%. The content of organic acid is 0.5% to 2.5%, The content of aluminum oxide is 59.0% to 90.0%.

10. The method according to claim 1, characterized in that: The properties of the catalyst in step (5) are as follows: the specific surface area is 170 to 280 m 2 / g, the pore volume is 0.6~1.3mL / g, the average pore diameter is 9~15nm, and the mechanical strength is 150~200N / cm.

11. The hydrogenation catalyst prepared by the method of any one of claims 1 to 10, preferably a residue oil hydrodemetallization catalyst or a residue oil hydrodesulfurization catalyst.

Citation Information

Patent Citations

  • Method for recycling waste hydrogenation catalyst

    CN105709853A

  • Preparation method of hydrogenation catalyst

    CN108067272A

  • Preparation method of high-activity hydrodemetallization catalyst

    CN113976137A

  • Hydrodesulfurization catalyst as well as preparation method and application thereof

    CN116060059A

  • Recovery method of valuable elements

    JP2022142809A